Hydrodynamic Forces acting on Two Flexible Free-hanging Cantilevers in Tandem Configurations due to Cross-flows - Prastianto, Rudi Walujo (IPTEK The Journal for Technology and Science, 2025)
The experimental study has been performed on two flexible free-hanging circular cantilevers in tandem configurations subjected to uniform cross-flows. The experiment was intended to investigate the time-dependent forces characteristics acting on the cylinders due to VortexInduced Vibration (VIV) phenomenon. The tests cylinders have free bottom-end conditions and can freely oscillate. The motions of the cylinders are evaluated as a bidirectional motion, in-line and transverse to the flow. Each cylinder has a length-to-diameter ratio of 34.4 with a low mass ratio of about 1.24. Based on cylinder’s diameter and free-stream flow velocities, the Reynolds number varied from 10,800 to 37,800. For examining Wake Induced Vibration (WIV) on the induced forces characteristics, five different gaps between the cylinders were employed. New various findings indicated that the dynamics of the present two free-hanging cantilever cylinders in tandem configurations are unique and definitely different to those other tandem configurations of either, two stationary cylinders or a transverse-only motion downstream cylinder lies behind a stationary upstream one.